Discovery Learning Method On Students’ Writing Narrative Text Ability - Nasution, Aisyah; Hamka, Hamka; Sinaga, Yusni (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to analyze the effect of the discovery learning method on the ability of students to write narrative texts. This type of research is an experimental study with a pre- experimental design. This study was conducted in one class only, by conducting a pre-test and post-test to measure students' writing skills before and after the application of the discovery learning method. The results showed a significant increase in students' average scores, where the average pre-test score was 42.46 and the average post-test reached 57.54. Analysis using the t-test showed that there was a significant difference between the two tests, proving that the discovery learning method is effective in improving students' narrative writing skills. This study is expected to contribute to the development of more innovative learning strategies in the context of modern education.